(untitled) (Південний архів (історичні науки), 2025)
The purpose of the article is to analyze in detail the texts of all issues of the Bulletin of the Museum of Sloboda Ukraine named after H. S. Skovoroda in order to publish little-known details of the work of this institution. The methodological basis of the work is founded on the general scientific principles of historicism, objectivity, and systematicity, as well as specialized historical methods: the problem-historiographical and comparative-historical approaches. Results. Articles of employees of the Museum of Sloboda Ukraine named after H. S. Skovoroda, published in the Bulletin of the museum, in form and content were often reports-chronicles. The 1920s were a time of active search and innovation in the museum work, which was reflected in the publications of the Bulletin. The authors of the articles raised the issue of organizing ethnographic expeditions, the need for a more active survey of Slobozhanshchina by local historians, the activation of exhibition, lecture and other types of educational work, etc. The Bulletin is an important historical source, as it contained important and reliable information on the history of the creation and operation of the H. S. Skovoroda Museum of Sloboda Ukraine before 1928. Thanks to the purposeful, versatile work of its employees, the G. S. Skovoroda Museum of Sloboda Ukraine in the 1920s became not only one of the main museums of the Republic, but also actually a research institution. Conclusions. The analysis of the articles of the staff of the Museum of Sloboda Ukraine named after H. S. Skovoroda, published in the Bulletin of the museum, testifies to the active work of its employees in many areas: successful replenishment of funds; conducting a large number of consultations, lectures, excursions, exhibitions in the 1920s; effective research, memorial protection and publishing. Thanks to mutual assistance, the Ethnological and local history section of the Kharkiv Research Department of the history of Ukrainian culture and the Museum of Sloboda Ukraine became centers of ethnological and local history research in Kharkiv region in the 1920s.